Electrochemical Synthesis of 2-Hydroxy-para-terphenyls by Dehydrogenative Anodic C–C Cross-Coupling Reaction - Lips, Sebastian; Franke, Robert; Waldvogel, Siegfried R. (Synlett, 2019)
The anodic C–C cross-coupling reaction provides fast access to a wide range of bi- and terarylic scaffolds by electrochemically mediated arylation reactions. Herein, a metal- and reagent-free electrosynthetic protocol for the synthesis of nonsymmetrical 2-hydroxy-para-teraryl derivatives is presented for the first time. It is scalable, easy to conduct, and allows the use of a broad variety of different functional groups.
Keywords: C–C coupling; protecting groups; electrochemistry; C–H activation; arylation; terphenyls